Analisis Sanad Matan Hadis Doa Sehari-Hari Buku Panduan Doa Paud TK Aisyiyah Sidoarjo - Muhlasin Amrullah; Khizanatul Hikmah; Diny Puspadewi (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to 1) Develop a daily prayer manual for TK-PAUD Aisyiyah sidaorjo 2) describing the hadith of prayers in the daily prayer book of Aisyiyah sidaorjo TK-PAUD. The subject of the study is a daily prayer guidebook dikdasmen aisyiyah sidaorjo area while the subject which is the primary source is the book of hadith. This research is literature, while this research method uses takhrij hadith method, which is to extract / trace all the sources of hadith from the books of hadith, with this methodology will be able to know the origin / source of hadith used as a prayer foundation in the prayer manual. Based on the research, the number of prayers in the prayer manual is 24 prayers, of which 4 prayers taken from the Qur'an include: Prayer of peace of mind, Prayer of kindness in the Hereafter, Prayer in vehicle, and Prayer of both parents of 4 prayers practice only the prayer of the parents of the prayer prayer must refer to the original verse. Whereas the other 20 prayers taken from the hadith include: Prayer before eating, Prayer after meal, Prayer forgetting to read prayers before eating, Prayer closing prayer, Prayer going to sleep, Prayer getting up, Prayer entering the house, Prayer going out, Prayer entering the l exit wc, prayer after ablution, iftitah prayer, prayer after hearing the call to prayer, prayer tasyahud, prayer after prayer, prayer when dressed, prayer in mirror, prayer in and out of the mosque, prayer visit sick people. of all hadith Prayers of prayer in the books of prayer are found in the hadith which are shohih, hasan, even some hadiths are weak, interceded by prayer: Praying in mirror, Prayer entering the house. In responding to this hadith, it is better to replace prayer with a general pronunciation, namely recitation of basmalah.